Spatial Knowledge: A Tool for Community Planning and Addressing Environmental Issues in Regional Context? - Nirwansyah, Anang Widhi; Andriani, Ana; Wuliandari, Juli Rochmijati; Mandili , Abdel; Sriyanto, Sriyanto (Journal of Regional and City Planning, 2025)
This study investigates the implementation of participatory mapping activities with indigenous communities to uncover their spatial understanding of environmental issues in regional context. By combining participatory GIS with a phenomenological approach, the research aims to extract critical environmental concerns and develop prioritization schemes for planning and conservation efforts, particularly in forest and small island communities. Two case studies were conducted: the Orang Rimba community in Jambi, Indonesia, and the Lovongai community in New Ireland Province, Papua New Guinea. Workshops and training sessions were held with small group in each community to identify and discuss local environmental challenges. The study revealed that the Orang Rimba community primarily concerns the decline of medicinal plant species and the threat on animal habitats, while the Lovongai community faces the pressing threat of sea-level rise. Through participatory mapping and collaborative efforts with local governments and NGOs, both communities developed potential solutions to address their respective environmental issues. It is recommended that future studies explore the long-term impacts of participatory mapping initiatives on community empowerment, environmental stewardship, and sustainable development.